(untitled) (Scientific journal of the Fergana State University, 2024)
This article delves into the captivating realm of axiology within phraseological units, shedding light on the intricate relationship between language and values. Language, traditionally viewed as a means of communication, is here unveiled as a mirror reflecting a societyʼs values, beliefs, and norms. This article underlines that values are not abstract concepts but guiding principles that influence our actions and decisions, deeply interwoven with the language we employ. The interplay between axiology and language transcends mere communication, transforming language into a dynamic reflection of our values.